Peran Pelatihan Dan Workshop Bagi Peningkatan Motivasi, Inovasi Dan Kreativitas Pada Umkm Kerajinan Tangan Dari Manik-Manik - Santi Riana Dewi; Andari Andari; Martina Rahmawati Masitoh (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2019)
This community service is carried out by lecturers at the university, in order to participate actively in improving the quality of human resources through counseling and workshops. Counseling and workshops carried out are related to efforts to increase motivation, innovation and creativity in MSMEs, especially handicrafts made from beads. The results of MSMEs in the form of handicrafts from beads are still very much needed to be continuously improved. Besides that the market for bead creativity products is still very widely opened. The results of these beadsare  in the form of prayer beads and various women's jewelry such as bracelets and necklaces. The handicrafts are chosen because the method of making them is quite easy and the ingredients needed are easy to obtain. The method used in this service is participatory approach, and the respondents consist of the community as business actors. Respondents also participated directly in the focus group discussion, interviews, training, workshops, consuls, and executions. Through the implementation of this service it is hoped that it will be able to encourage the growth and development of MSMEs to improve community welfare and improve the quality of the active role of lecturers as a form of concern for improving the quality of human resources in the community.